Commodification of Children on Social Media Endorsement (Case Study on @zaskiaadyamecca's Instagram Account) - Nurul Akmalia; Septia Ardiani (2021)
This study explores how commodification practices occur through promotional uploads or commonly known as endorsements on social media accounts of public figures (influencers). Influencers, as people who are considered capable of influencing the audience, take advantage of this fame to carry out promotional practices that involve their families, even their children. This economic practice is not only considered as exploitation, but is specifically known as the commodification of children. The presentation of this research was carried out using a case study approach on one of the Instagram influencer accounts, Zaskia Adya Mecca. Uploads on her Instagram with handle called @zaskiaadyamecca were analyzed using the social semiotics method with derivatives of visual communication analysis tools. Document studies were also conducted on Zaskia's promotional or endorsement fee involving her family and children. This information is secondary data to provide validation for arguments regarding commodification practices communicated visually through Instagram. The results of the research based on visual communication and document studies are that the practices on the Instagram account is indicated to be commodifying children.